Social Responsibility and Influences on Finantial Returns: A Study on the Sustainability Performance Indicators - Fernandes, Anderson Rocha de Jesus (2018)
This study presents an analysis of performance and randomness of the sustainability’s series indexes concerning to prices of the major stock exchanges worldwide. The approach was performed by applying a variance ratio test in order to evaluate the autocorrelation of each series. Historical data of the ISE, DJSI, FTSE4Good and JSE SRI Indexes were used. Those indexes belong, respectively, to the stock exchanges of São Paulo, New York, London and Johannesburg. The information was collected in the Wall Street Journal database. The results indicated that there is no evidence of the indices’ series randomness. Sustainability indexes have different variances when compared to the main indices, however, are lower only for ISE and FTSE4Good.